RIO - what an OER story: - Sanchidrián, Monica (My University, 2023)
Poster abstract for Open Science FAIR 2023. 'RIO: What and OER Journey' presents the development of a compulsory, internal module for all TCD incoming doctoral students to a re-useable, scalable, FAIR Open Educational Resource.
Keywords: Open Educational Resource (OER); Research Integrity tarining; Scholarly communication training